1997
DOI: 10.1103/physreve.55.5448
|View full text |Cite
|
Sign up to set email alerts
|

Parametric forcing of waves with a nonmonotonic dispersion relation: Domain structures in ferrofluids

Abstract: Surface waves on ferrofluids exposed to a dc-magnetic field exhibit a nonmonotonic dispersion relation. The effect of a parametric driving on such waves is studied within suitable coupled Ginzburg-Landau equations. Due to the non-monotonicity the neutral curve for the excitation of standing waves can have up to three minima. The stability of the waves with respect to long-wave perturbations is determined via a phase-diffusion equation. It shows that the band of stable wave numbers can split up into two or thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…The mechanism of parametrically driven surface waves in these experiments is similar to the one reported earlier for ferrofluids [16,17]. A major difference, however, is the fact that the dominant response of a ferrofluid to external vertical magnetic driving comes at half frequency, as does that found in vibrated water and sand layers (harmonic response was reported for the free surface of a ferrofluid driven with the parallel ac magnetic field [18]).…”
supporting
confidence: 82%
“…The mechanism of parametrically driven surface waves in these experiments is similar to the one reported earlier for ferrofluids [16,17]. A major difference, however, is the fact that the dominant response of a ferrofluid to external vertical magnetic driving comes at half frequency, as does that found in vibrated water and sand layers (harmonic response was reported for the free surface of a ferrofluid driven with the parallel ac magnetic field [18]).…”
supporting
confidence: 82%
“…A separation of the surface wave into different phases has recently been predicted for parametrically excited surface waves [4]. This intriguing result is due to a non-monotonic dispersion relation for surface waves, which means that up to three different wave numbers can be excited with one single driving frequency.…”
mentioning
confidence: 95%
“…At this point, we note that a recent theoretical study has shown that parametrically driven surface waves on ferrofluids can be unstable to multiple spatial modes simultaneously [10]. Here, the existence of multiple unstable modes originates from the non-monotonic dispersion relation of ferrofluids.…”
mentioning
confidence: 99%
“…In our experiments, coexisting domains with different wavevectors are only observed in bistable regions. In order to check the feasibility of this hypothesis, we have extended the earlier theoretical study by Raitt and Riecke [10] to two-dimensional space and have found a parameter regime in which well defined rhombic patterns are globally stable [14]. Recently, Lifshitz and Petrich have also demonstrated the existence of a stable rhombic pattern in a generic model system containing two unstable spatial modes [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation